Amorphous Roxithromycin Loaded in-situ Gel for the Treatment of Staphylococcus aureus Induced Upper Respiratory Tract Infection - Ji L; Bai H; Tao N; Lei Y; Li A; Wang C; Cui P; Gu X (Infection and Drug Resistance)
Li Ji,1 He Bai,2 Ning Tao,2 Yanpeng Lei,2 Anyin Li,2 Cheng Wang,2 Pengfei Cui,2 Xiaofeng Gu1 1Department of Otolaryngology, The Affiliated Changzhou No. 2 People’s Hospital of Nanjing Medical University, Changzhou, 213003, People’s Republic of China; 2School of Pharmacy, Changzhou University, Changzhou, 213164, People’s Republic of ChinaCorrespondence: Pengfei Cui, Email cuizy1990@cczu.edu.cn Xiaofeng Gu, Email xiaofenggu2006@163.comObjective: Upper respiratory tract infections are among the most prevalent respiratory diseases, imposing both financial and physical burdens on affected individuals. Roxithromycin (ROX), a primary drug for treating bacterial-induced respiratory tract infections, is typically administered orally due to its hydrophobic nature. However, the non-specific distribution resulting from oral administration reduces bioavailability and can cause side effects such as diarrhea.Methods: In this study, we prepared a thermo-sensitive in-situ gel using a facile and highly reproducible method by simply mixing two types of poloxamers with ROX.Results: The ROX can be well dissolved in the poloxamer matrix in amorphous state to give solution. Upon intranasal administration, the ROX solution undergoes a phase transition to form in-situ gel under body temperature. This gel remains in the nasal cavity for an extended period, releasing the drug directly to the site of infection and minimizing non-specific distribution. Pharmacokinetic experiments revealed that, compared to oral administration, the bioavailability of local nasal administration increased by 1.5 times, and the drug concentration in the local nasal cavity increased by 8 times. In contrast, concentrations in the liver and small intestine did not significantly differ from those following oral administration. In vivo antibacterial experiments also showed that the ROX in-situ gel has superior antibacterial efficacy and excellent biocompatibility.Conclusion: These results suggest that the thermo-sensitive ROX in-situ gel is a promising formulation for treating bacterial upper respiratory tract infections.Keywords: roxithromycin, in-situ gel, bacterial infection, upper respiratory tract